AUTOMATION OF THE ACCOUNT SUITABILITY OF THE VARIETY PARAMETERS TO SPREAD OF UKRAINE - Golub, B.; Trokhymenko, V. (Енергетика і автоматика, 2016)
Considered automation of accounting indicators life varieties to spread of Ukraine and described the stages of their implementation. Depicted main blocks of life indicators accounting varieties on which the designed topology and use case diagram. An improved software and the use of modern OLAP-technologies to analyze the data that will be based on data repository.